Evaluation of inoculum acclimatation and biochemical seasonal variation for the production of renewable gaseous fuel from biorefined Laminaria sp. waste streams. (August 2019) - Tedesco, S.; Daniels, S.
Abstract: Laminaria . sp. seaweeds have been recognised the potential to greatly contribute to the generation of renewable gaseous fuel via anaerobic digestion. Seaweed feedstock has been documented to consistently vary its biochemical composition with seasons, which affects stability of biomethane production. As currently seaweeds are too costly for use as third generation feedstock for biofuels, this paper investigates the biogas potential of the algal waste streams from the existing bio-industry. Analytical tests identified an improved digestibility of extracted residues (C:N > 20). Fermentation with and without inoculum acclimatation revealed the interaction between compositional seasonality and inoculum type to significantly affect methane production from the extracted samples. Summer's composition has the most significant impact on methane production, with best results achieved with acclimatised inoculum (433 ml CH4 gVS −1 and final biodegradation of about 90%). Organics concentration (tCOD) and ash:volatile (A:V) ratio also play a major role in the bioconversion process. In particular, digestion with acclimatised inoculum better responds to A:V fluctuations across seasons, which produced the highest average methane yield of 334 ml gVS −1 . Pretreatments are required to increase the biodegradation index in spring and summer when not using acclimatation. Highlights: Biorefined L. hyperborea residues demonstrated improved digestibility (C:N > 20). Seasonal composition and inoculum type to significantly affect methane production. The ratio of ash to volatile solids in spring and winter of 0.21 is the lowest recorded. Summer yielded the most with 433 ml CH4 gVS −1 with acclimatised inoculum.